Balancing access with accuracy for infant HIV diagnostics in Tanzania (A) - Palamountain, Kara; Waikar, Sachin; Hanson, Andrea; Nelson, Katherine ([London] : SAGE, 2016)
The Global Health Initiative (GHI) is a tripartite collaboration among Northwestern University, non-profit donors, and commercial diagnostics companies. GHI attempts to bridge the gap between the market for sophisticated medical diagnostics equipment in wealthy nations and the need for point-of-care diagnostics in resource limited settings. In 2006 GHI narrowed its focus to HIV diagnostics for underserved nations. The case examines the accuracy-access trade-off related to the roll-out of infant HIV diagnostics in Tanzania.
Originally Published in: Palamountain, K., Waikar, S., Hanson, A., & Nelson, K. (2008). Balancing Access with Accuracy for Infant HIV Diagnostics in Tanzania (A). 5-308-502(A). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Global Helth Initiative (Project); New products -- Case studies; Product design -- Case studies; HIV infections -- Diagnosis -- Tanzania; HIV-positive children -- Services for -- Tanzania